The influence of food dimension (texture and volume) from processed rice (rice, lontong, and ketupat) to the perception of satiety and consumer satisfaction level - Kiki Fibrianto; H Syahrastani; Lutfiani A. Nisa; Laila Y. Wahibah (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2019)
It has been commonly perceived for majority Indonesian public that unless eating steamed-rice, they would not be feeling full. This current study aims to investigate possible reasons in sensory perspective to understand that public perception on satiety of Indonesian traditionally rice products, including steamed rice, ‘lontong’ and ‘ketupat’. Samples were presented by both same amount of mass (iso-mass) and same amount of calorie (iso-calorie), which allows modifying satiety perceptions. The assessment was conducted by measuring modified Visual Analogue Scale (VAS). Based on Pearson Correlation method, the result indicates that satiety perception tends to be affected by dimensions (volume of rice products) in both iso-mass and iso-calorie servings (α<0.05). However, the level of satisfaction did not showed a strong correlation to any physical parameters of samples. Therefore, it is suggested that psychological driven factor such as food habit is more dominating in terms of rice satiety in Indonesia rather than metabolic factor.